Effects of Common Anti-epileptic Drugs on the Serum Levels of Homocysteine and Folic Acid - Paknahad, Zamzam (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: Elevated total plasma homocysteine has been established as an independent risk factor for CVD. A strong relationship between plasma homocysteine levels and mortality has been reported in patients with CAD. Interference with folate and homocysteine metabolism by some drugs, may lead to increased plasma homocysteine levels. The object of the study was to examine the effect of AEDs on the serum concentrations of folic acid. METHODS: A total of 22, older than 18-year-old, epileptic patients, admitted in the Neurology Clinic, who were treated with AED at least for one year were selected. Twenty-two sex- and age-range-matched controls were enrolled in the study. Concentrations of total homocysteine and folic acid in the serum were measured in a fasted status. Demographic and medicine information was collected via a questionnaire. Data were analyzed by spss(16) software. RESULTS: Mean of serum Hcy concentration in the patients was significantly higher compared to that in the controls (p = 0.04). Serum folic acid had a nonsignificant negative correlation with the dose of drug used (p = 0.2). Serum homocysteine was not significantly correlated with the dose and duration of drug consumption (p values were 0.4, 0.24, respectively). Serum homocysteine was not significantly correlated with the kind of drug (p = 0.4), but folic acid concentration was significantly lower in the monotherapy group than in the poly therapy group (p = 0.02). CONCLUSIONS: Homocysteine (Hcy) was not different between the epileptic and nonepileptic groups, although the means of the serum folic acid were similar. Possible mechanisms by which AEDs could cause hyper-homocysteinemia might be through the dysfunction of homocysteine metabolism, the acceleration of vitamin metabolism, and the interference in the metabolism of folic acid coenzymes.